An unusual presentation of gastric mucosa-associated lymphoid tissue (MALT)-type lymphoma - Bikram Shrestha; Bernard Kim; Alison Huffstetler (Greater Baltimore Medical Center, 2016)
Mucosa-associated lymphoid tissue (MALT)-type lymphoma is a relatively rare disease; nevertheless, it is the third most common lymphoma type, accounting for 5-7% of all non-Hodgkin lymphomas. Case series and retrospective analysis published in the literature have suggested that extra gastrointestinal (GI) MALT-type lymphoma can occur simultaneously with MALT-type lymphoma involving the GI tract. We report the case of a healthy, 64-year-old Caucasian male who presented with progressive fatigue, non-productive cough, and worsening exertional shortness of breath for 3 months who was subsequently diagnosed with gastric extra-nodal marginal zone B-cell lymphoma or MALToma with simultaneous metastasis to the lung (bronchi) based on biopsy reports. Case presentation: A 64-year-old Caucasian male presented to the emergency room complaining of progressive fatigue for 3 months which had progressed to the point of hindering his usual activities of daily living (ADL). He had recently visited his primary care provider for evaluation of a non-productive cough and exertional shortness of breath. A chest radiography obtained at the time showed bilateral infiltrates. He was then treated for atypical pneumonia but his symptoms unfortunately did not improve. Initial investigations in the emergency room revealed severe anemia and a positive stool guaiac test. Imaging showed bilateral pulmonary infiltrates and an irregular gastric mass. Gastric and transbronchial biopsies were suggestive of extra-nodal marginal zone B-cell lymphoma with simultaneous metastasis to the bronchi. He was treated symptomatically with transfusion of packed red blood cells (PRBC) and intravenous iron followed by radiotherapy. Helicobacter pylori infection was ruled out eliminating the possibility of treating him with eradication therapy. Conclusion: Although the stomach is the most common and most extensively studied site of involvement of MALT lymphomas, they can also emerge in many other locations. MALT lymphomas have a high tendency to disseminate to other sites; therefore, extensive staging may be necessary to look for suspicious lesions.